Analisis Pengungkapan Sukarela pada Bank Umum Syariah di Indonesia - Muhammad Haidir Ali; Ahmad Tarmidzi Lubis (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2015)
This study is a descriptive study to assess voluntary disclosure in annual reportsIslamic Banks (iB) with that should be disclosed. Annual reports used in this study isan annual report iB in Indonesia in 2011, 2012, and 2013. This research is relativelynew because no one has done research on voluntary disclosure in Islamic Banks (iB).Therefore, in order to study to obtain maximum results, the coding instructions forvoluntary disclosure must be in accordance with the study conducted by Rr. PuruwitaWardani (2012) entitled